Go luck yourself - Raasch, Sara (A royals and romance novel, 2025)
"Someone has been stealing Christmas's joy, and there's only one clue to the culprit -- a single shamrock. With Coal busy restructuring Christmas--and their dad now having a full midlife crisis in the Caribbean -- Kris volunteers to investigate St. Patrick's Day. His cover: an ambassador from Christmas to foster goodwill. What could go wrong? Everything, it seems. Because Prince Lochlann Patrick, Crown Prince of St. Patrick's Day, happens to be the mysterious student that Kris has been in a small war with at Cambridge. They attempt to play nice for the tabloids, but Kris can't get through one conversation without wanting to smash Loch's face in--he's infuriating, stubborn, loud, obstinate, hot -- Wait -- hot? Kris might be in some trouble. Especially when it turns out that the mystery behind Christmas's stolen magic isn't as simple as an outright theft. But why would a Holiday that Christmas has never had contact with, one that's always been the very basis of carefree, want to steal joy? Can a spare prince even hope to unravel all this, or will Kris lose something way more valuable than his Holiday's resources -- like his heart?"--Amazon.